Carnal, bloody and unnatural acts: religious pollution in ancient Rome - Lennon, Jack (2011)
The aim of this thesis is to define and explore the nature of pollution and purity in pre-Christian Roman religion, focussing particularly on the late Republic and the early Principate. In spite of the established position of these themes in studies of Greek religion, there remains no comprehensive treatment of pollution and purity in Roman religion. The thesis exploits the approaches established by modern anthropology and classical philology to examine several aspects of religious pollution, focussing primarily on the role of the human body within religious activity.